Rare and Personal Collections at National Library of Malaysia - Nordin, Nordiana Mohd; Nasharudin, Nurhidayah; Mohd Zaki, Faddliza (Perpustakaan Hamzah Sendut, 2016)
This paper aims to explore the characteristics of rare and personal collections or known as Malaysiana Collections at National Library of Malaysia (PNM). The explanations on definition, type of collections, policies or acts that related to rare materials collection, the challenges faced by National Library of Malaysia in acquiring the rare collection, acquisition of rare collection and promoting the collection to the public discussed. The review from this paper will expose to the audience about the rare and personal collections in Malaysia as a whole. Other than that, the several issues and challenges on maintaining and managing on rare materials will discuss in detailed. Hence, this paper will give the positive impact and awareness to people about the importance and knowledge on how to manage, preserve and appreciate the rare and personal collections that have significant to the future generations on country’s heritage and ancient history.